DIPLOMASI ORANGUTAN MALAYSIA DALAM PERSPEKTIF EKOLOGI BUDAYA: SEBUAH TINJAUAN KRITIS TERHADAP IMPLIKASI EKSPANSI KELAPA SAWIT - Abimanyu, Akhdiat Dimas (Multikultura, 2026)
This study examines the phenomenon of Malaysia's orangutan diplomacy as part of public diplomacy and cultural diplomacy in the face of international pressure on the palm oil industry, particularly from the European Union. Inspired by animal diplomacy practices such as China's panda diplomacy, Malaysia in 2024 initiated a plan to make the orangutan a diplomatic symbol to build a positive image and strengthen trade relations with partner countries. This study uses a qualitative descriptive approach with a literature review method that utilizes academic sources, policy documents, non-profit organization reports, and mass and social media. The analysis is conducted through a cultural ecology perspective to understand the relationship between economic and political interests, diplomatic practices, and their impact on the ecology and local communities. The results of the study indicate that orangutan diplomacy has the potential to reduce the animal to a symbolic instrument of the state, while simultaneously obscuring structural problems such as deforestation and the expansion of oil palm plantations that threaten the orangutan's natural habitat. Objections from various conservation organizations state that without a strong commitment to in situ conservation and forest ecosystem protection, this diplomacy tends to be symbolic and counterproductive. This article argues that animal diplomacy should not be separated from ecological and cultural responsibilities, especially in the context of environmental ecosystems and the relationship between people and animals as part of a shared ecological system.